Do Chinese Traditional and Modern Cultures Affect Young Adults’ Moral Priorities? - Hu, Xiaomeng; Chen, Sylvia Xiaohua; Zhang, Li; Yu, Feng; Peng, Kaiping; Liu, Li (Frontiers in Psychology, 2018)
Dramatic cultural change has occurred in Mainland China over the past four decades, yet little is known about how this cultural shift impacts Chinese peoples’ moral values. The present research aims to fill this gap by examining whether Chinese traditional and modern cultures influence young adults’ moral judgments. Study 1 investigated the relation between psychological traditionality/modernity and moral concerns. Results indicated that participants who strongly endorsed Chinese traditional culture prioritize relationship concern rather than justice concern. Study 2 used the cultural priming method and tested the effects of traditional and modern icons on moral concerns. Results suggested that participants who were primed with traditional or modern or neutral icons did not give priority to relationship or justice concern. Together, our findings provide initial empirical evidence on whether Chinese traditional and modern cultures shift the moral mindsets of bicultural young Chinese among alternative (and even competing) moral codes.